2009
DOI: 10.1007/s11274-009-0043-1
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative methodologies for determination of airborne microorganisms at concentrated animal-feeding operations

Abstract: The generation of airborne microorganisms from concentrated animal-feeding operations (CAFOs) is a concern from a human and animal health perspective. To better understand the airborne microorganisms found in these environments, a number of collection and analytical techniques have been utilized and will be discussed in this review. The most commonly used bioaerosol collection method is the liquid impingement format, which is suitable with a number of culture-based and non-culture molecularbased approaches, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 130 publications
1
22
0
Order By: Relevance
“…qPCR values were about 3 logs greater than those determined by the MPN technique (a statistically significant difference; P Ͻ 0.0001), which indicated that the majority of enterococci might have gone into a VBNC state such as was seen in earlier studies involving bovine feces and manure (28,30). However, since the DNA could also have been extracted from damaged or dead cells, qPCR analysis may have resulted in overestimation of actual titer values in the samples (7,31,37).…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…qPCR values were about 3 logs greater than those determined by the MPN technique (a statistically significant difference; P Ͻ 0.0001), which indicated that the majority of enterococci might have gone into a VBNC state such as was seen in earlier studies involving bovine feces and manure (28,30). However, since the DNA could also have been extracted from damaged or dead cells, qPCR analysis may have resulted in overestimation of actual titer values in the samples (7,31,37).…”
mentioning
confidence: 77%
“…qPCR is often used as a convenient alternative to culture-dependent techniques that has the added advantage of being able to detect viable but nonculturable (VBNC) cells of potential pathogens (7,27,59). While there are documented advantages and disadvantages with both molecular method-and culture-dependent approaches, it was our intent to provide the first quantitative survey of selected bacterial indicators and putative pathogens in dairy wastewaters.…”
mentioning
confidence: 99%
“…The conventional PCR assay has been applied to analyse air samples for the presence of airborne mycobacteria [78] and fungi commonly associated with adverse health effects [79]. PCR allows the detection and identification of non-culturable airborne microorganisms; it does not allow distinguishing between non-viable and viable microorganisms [80]. Currently, the real-time PCR (RT-PCR) is evolving into a promising tool capable of reproducible and accurate measurements of total microorganism concentrations in environmental samples.…”
Section: Polymerase Chain Reaction (Pcr) -Pcr Techniquementioning
confidence: 99%
“…While molecular-based methods such as quantitative PCR (qPCR) have increased sensitivity over traditional culture techniques, they cannot distinguish between inactive and infectious organisms. 17 Due to the difficulties in detecting airborne pathogens and deciphering positive results, many researchers instead target indicator organisms in bioaerosol studies. 12,18−20 However, the survival of airborne indicator organisms is likely different from that of pathogens, making them a poor pathogen surrogate.…”
Section: ■ Introductionmentioning
confidence: 99%